Effect of active application of self-etching ceramic primer on the long-term bond strength of different dental CAD/CAM materials - Tribst, João-Paulo-Mendes; Diamantino, Pedro Jacy Santos [UNESP]; De Freitas, Maiara-Rodrigues; Tanaka, Isabela-Vitelli [UNESP]; Silva-Concilio, Lais-Regiane; De Melo, Renata-Marques [UNESP]; Saavedra, Guilherme-De Siqueira-Ferreira-Anzaloni [UNESP] (Medicina Oral, S.L., 2021)
Background: The objective of this in vitro study was to evaluate the effect of the active application of self-etching ceramic primer (ME&P) on the bond strength of different dental CAD/CAM materials (Lithium Disilicate ceramic (LD), Leucite ceramic (LE), Zirconia reinforced lithium silicate ceramic (ZLS), and Hybrid ceramic (HC)) with thermocycling aging. Material and Methods: The samples were randomly divided into 16 groups (n = 20). Dual resin cement cylinders were made and light cured for 10 s (1.200 mW/cm2) for the shear bond strength test. 3-way ANOVA revealed that the factors were statistically significant (P < 0.05). Results: The aging process had a negative impact on the bond strength for all groups except for Lithium Disilicate, with active application. ZLS and LE showed promising results with high bond strength values for the ME&P active application; however, after aging the bond strength value was significantly reduced. HC showed reduced bond strength values regardless the ME&P application. Conclusions: In order to obtain a durable bond strength, the recommended protocol of 20 s of active application followed by 40 s of sitting time in the self-etching ceramic primer should be followed when using reinforced-glass ceramics as restorative materials.
Keywords: computer-aided design; dental materials; Dentistry; shear strength; silane